Pterigión y disminución visual en paciente de sexo femenino de 46 años. - Guilindro Coloma, Janina Roció (2022)
The pterygium is an abnormal growth of tissue on the surface of the eye that can affect your vision depending on the degree of invasion, the discomfort that the pterygium presents in addition to altering its aesthetics is burning, irritation, foreign body sensation, tearing and in many cases eye pain. Pterygium occurs more easily in people who are in constant outdoor activity such as: farm workers, construction workers, those who are constantly exposed to dust. The treatment given to the pterygium depends on the degree of invasion in which it is found, but in general, its treatment is always surgical. OBJECTIVE: to determine the refraction of the patient, her degree of pterygium, identifying its main causes, prevention and treatment. METHODOLOGY: An eye examination was performed through which we examined a 46-year-old female patient who presented discomfort such as: tearing, irritation and foreign body sensation in the right eye, in addition to presenting a decrease in visual acuity, for approximately 5 years. CONCLUSION: in conclusion we have the diagnosis of a III degree pterygium, caused by continuous exposure to sun and dust, which was referred to an ophthalmologist to follow up on their respective treatment, which is mostly surgical and their visual decrease is for presbyopia caused by his age, for which he was prescribed framed glasses.